2019
DOI: 10.1016/j.amjsurg.2018.11.007
|View full text |Cite
|
Sign up to set email alerts
|

Looks can be deceiving: Gaze pattern differences between novices and experts during placement of central lines

Abstract: Background: The objective of this study was to determine whether gaze patterns could differentiate expertise during simulated ultrasound-guided Internal Jugular Central Venous Catheterization (US-IJCVC) and if expert gazes were different between simulators of varying functional and structural fidelity. Methods: A 2017 study compared eye gaze patterns of expert surgeons (n=11), senior residents (n=4), and novices (n=7) during CVC needle insertions using the dynamic haptic robotic trainer (DHRT), a system which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 28 publications
3
10
0
Order By: Relevance
“…The differences between experts and novices found in our study coincide with those reported in CVA with other motion analysis systems for instruments and/or body parts, such as hand-track motion devices [15,22], gaze pattern analysis [23], and video analysis for eyehand coordination [24]. Specifically for 3D body motion tracking systems, as in our study, differences have been reported using body assessment in tracheostomy [17].…”
Section: Plos Onesupporting
confidence: 87%
See 1 more Smart Citation
“…The differences between experts and novices found in our study coincide with those reported in CVA with other motion analysis systems for instruments and/or body parts, such as hand-track motion devices [15,22], gaze pattern analysis [23], and video analysis for eyehand coordination [24]. Specifically for 3D body motion tracking systems, as in our study, differences have been reported using body assessment in tracheostomy [17].…”
Section: Plos Onesupporting
confidence: 87%
“…Indeed, motion analysis of procedures that depend heavily on instrument manipulation focuses on the instrument movement’s biomechanics instead of the hand’s motion [ 19 , 26 ]. Also, when visual coordination is a critical component of the procedure, other variables are measured, such as gaze patterns [ 23 ]. We believe that both analyses (instrument motion and eye-tracking) are necessary to further describe differences between experts and novices in stage 1.…”
Section: Discussionmentioning
confidence: 99%
“…16 Specifically within CVC placement, experts fixated more on the ultrasonography whereas novices spent time tracking the needle and ultrasound probe. 22 Contrary to the current literature on gaze patterns in procedural education, this study focused on supervising the IBP teacher. We found that the use of the eye-tracking device for assessment of gaze metrics among supervising teachers is feasible and likely has some utility given the potential signal suggesting differences in gaze patterns among IBP teachers.…”
Section: Discussionmentioning
confidence: 99%
“…The gaze data were mapped onto a still image [ 63 , 64 ] with assisted mapping feature [ 64 , 65 ]. After the assisted mapping was completed, we carefully checked the incorrect mapping points and manually re-mapped them [ 66 , 67 ].…”
Section: Methodsmentioning
confidence: 99%